A LEGAL ANALYSIS OF THE DRAFTING OF INTERNATIONAL COOPERATION DEEDS TO PREVENT BUSINESS DISPUTES (A Research Study in Batam City) - Rahaditya Reza Christianto; Ali Imran; Agus Siswanto Siagian (RADJA PUBLIKA, 2025)
Globalization has driven an increase in the intensity of international business cooperation involving various cross-border entities. In this context, international cooperation agreements play a crucial role as legal instruments capable of regulating relations between parties and mitigating potential disputes. Batam City, as a strategic free trade and free port area (KPBPB), plays a vital role in supporting cross-border business cooperation. However, in practice, the drafting of international cooperation agreements faces complex challenges in terms of regulation, implementation, and harmonization of the legal system. This research focuses on three main research questions: how the drafting of international cooperation agreements is regulated in Indonesia, how the drafting of international cooperation agreements is implemented, specifically in Batam City, and the obstacles and solutions encountered in drafting such international cooperation agreements. These three aspects are examined to understand the extent to which national and local legal systems can anticipate and facilitate the need for equitable and effective cross-border cooperation. The research methods used are normative juridical and empirical. Data were obtained through a literature review of legal regulations, doctrines, and theories, as well as fieldwork through interviews with notaries, legal practitioners, and relevant agencies in Batam City. This research employed a descriptive-analytical approach with qualitative analysis to describe the reality of legal practice and evaluate the effectiveness of drafting international cooperation deeds. The results indicate that regulations for drafting international cooperation deeds in Indonesia are not yet specifically regulated, leading to differing interpretations in the field. Implementation in Batam City still faces limited human resource capacity and a lack of synchronization between government agencies. The main obstacles include differences in legal systems, language, and a lack of international contract drafting standards. Therefore, it is recommended that the government develop comprehensive technical regulations, increase training for notaries, and strengthen cross-agency coordination to create legal certainty and prevent disputes in international business cooperation.